From Stage to Skin: Unpacking K-Pop’s Power as Ambassadors for Scarlett Skincare in Indonesia - Sylvia Samuel; Daniel Widjaja (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This research examines the impact of K-Pop celebrity endorsements on consumer purchase decisions within the Indonesian skincare market, specifically focusing on Scarlett Skin Care products. Using a quantitative research design, data were collected from 350 Indonesian consumers and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS. The results demonstrate that promotional activities exert the strongest and most statistically significant influence on purchase decisions, positioning promotion as a crucial driver of consumer interest in Scarlett products. While K-pop endorsements achieved high visibility and appeal among respondents, they displayed a negligible direct effect on purchase decisions, with a slight negative influence detected. Moreover, the interaction between income level and celebrity endorsement was found to be non-significant, indicating that the appeal of K-Pop endorsements does not vary substantially across income segments. Viral marketing also showed no significant moderation by income, with only a marginally significant interaction observed between income and promotion.